TINGKAT KESIAPAN GENERASI EMAS INDONESIA DI ERA DISRUPSI BERDASARKAN KARAKTERISTIK DIGITAL NATIVE - Hadjaratie, Lillyan; Hasdiana, Hasdiana; Masaong, Abd Kadim; Panai, Abdul Haris (Universitas Bina Taruna Gorontalo, 2023)
This study aims to measure the level of student generation Z with Digital Native characteristics, which are limited to active students in Odd Semester 2022/2023 Information Technology Education Study Program (ITE) and Visual Arts Education Study Program (VAE) Faculty of Engineering, State University of Gorontalo, who will reach the age of 40 to 45 years in 2045 (Golden Generation). The research method used is descriptive quantitative. The results showed that ITE and VAE Study Program students were at a